Prototyping PISA-like Mathematics Problems for 8th-grade Students Using Javanese Context - Afit Istiandaru; Vita Istihapsari (Universitas Ahmad Dahlan, 2022)
Javanese context is rich of phenomena potentially used as a starting point to learn mathematics. On the other hand, the Indonesian students’ performance in PISA is consistently low due to the small number of PISA-like problems which can be used to foster the students’ mathematical literacy measured in PISA. Therefore, this research aims to develop a set of PISA-like problems using the Javanese context targeted for 8th-grade students of Junior High School. It is a development study using Plomp’s framework in the stage of need analysis and prototyping. We have successfully developed a prototype of PISA-like mathematics problems using Javanese context. There are six items covering seven basic competences in the 8th-grade of junior high school. The items used various mathematics skills such as communication, representation, mathematization, devising strategies, and reasoning. We could explore some Javanese contexts such as traditional building, transportation, calendar system, community meeting, and historical place. Meanwhile the school mathematics materials include number sequence, Cartesian coordinate, relation, linear function, linear equation system in two variables, and Pythagorean theorem.